Risperidone and Social Outcome in Schizophrenia: A One Year Follow-up Study - Shrivastava, Amresh (International Journal of Psychosocial Rehabilitation, 2014)
Risperidone has been found to be effective in the management of schizophrenia across various studies. Most of these studies have looked at the clinical outcomes in patients with schizophrenia. The emphasis has always been on improvement in clinical features is usually primarily assessed by various rating scales. Most of these studies are of 8-12 weeks duration and report short-term outcomes. One should also assess the improvement on various psychosocial measures as clinical improvement may not give the clear picture of recovery. It is also important to look at the long-term outcome in schizoprenia. So the present study was envisaged with the intention to study the clinical as well psychosocial outcome at the end of one year in patients of schizophrenia on Risperidone. 50 consecutive patients of schizophrenia, diagnosed as per the DSM-IV criteria, fulfilling the selection criteria were followed-up and treated with Risperidone over a period of one year. Improvement was assessed using Positive and Negative Symptom Scale (PANSS), Clinical Global Improvement – Severity (CGI-S) and seven psychosocial parameters viz. social functioning, productivity, economic independence, education, suicidality, re-hospitalization and exacerbation. Predefined operational criteria were used to rate the patients on these seven psychosocial parameters. A statistically significant improvement was noticed with Risperidone therapy on PANSS and CGIS at the end of study period of one year. This was associated with a clinically significant improvement on all the various psychosocial parameters. A significant improvement was observed on clinical as well as psychosocial parameters in the patients of schizophrenia over a period of one year with Risperidone therapy.